MEMBANGUN PERAN GURU MELALUI SOSIOLOGI PENDIDIKAN - Zulmawati Zulmawati (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2018)
ABSTRACTIn the world of education student development is influenced by parents, teachers, society. For this reason, teachers must understand and be equipped with educational sociology and skilled in operating it in educational activities. A teacher also has a very important role in creating an atmosphere in school life. By understanding the sociology of education the teacher is expected to know ways - how to control the educational process to develop individual personalities to be better. So that the fundamental problems of education can be overcome, therefore teachers as educators must try to analyze education from the sociology of education. Keywords: Educational Sociology, Teacher, Teacher's RoleABSTRAKDalam dunia pendidikan perkembangan siswa dipengaruhi oleh orang tua,guru,masyarakat. Untuk itu, para guru harus paham dan dibekali dengan sosiologi pendidikan serta terampil mengoperasikannya dalam kegiatan pendidikan. Seorang guru juga mempunyai peranan yang sangat penting dalam menciptakan suasana dalam kehidupan sekolah. Dengan memahami sosiologi pendidikan guru diharapkan akan mengetahui cara – cara mengendalikan proses pendidikan untuk mengembangkan kepribadian individu agar lebih baik. Sehingga masalah – masalah pendidikan yang fundamental dapat teratasi, oleh karenanya guru sebagai tenaga pendidik harus berusaha menganalisis pendidikan dari sosiologi pendidikan. Kata Kunci: Sosiologi Pendidikan, Guru, Peran Guru